2011
DOI: 10.1007/s11244-011-9688-8
|View full text |Cite
|
Sign up to set email alerts
|

Structures, Mechanisms, and Kinetics of Ammoxidation and Selective Oxidation of Propane Over the M2 Phase of MoVNbTeO Catalysts

Abstract: We report here first-principles-based predictions of the structures, mechanisms, and activation barriers for propane activation by the M2 phase of the MoVNbTeO multi-metal oxide catalysts capable of the direct conversion of propane to acrylonitrile. Our approach is to combine extensive quantum mechanical (QM) calculations to establish the mechanisms for idealized representations of the surfaces for these catalytic systems and then to modify the parameters in the ReaxFF reactive force field for molecular dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 31 publications
(27 reference statements)
2
16
1
Order By: Relevance
“…13 However it is in sharp contrast to previous suggestions for vanadium 22 and molybdenum oxides, 23 that oxygen bound directly with V or Mo are responsible for initial alkane C-H activation.…”
Section: Vanadium-rich Te=o Regionmentioning
confidence: 76%
“…13 However it is in sharp contrast to previous suggestions for vanadium 22 and molybdenum oxides, 23 that oxygen bound directly with V or Mo are responsible for initial alkane C-H activation.…”
Section: Vanadium-rich Te=o Regionmentioning
confidence: 76%
“…So far, however, only a handful of theoretical studies have been performed to better understand the catalytic behavior of the Mo-V-Te-Nb-O M1 and M2 phases [10][11][12][13][14]. Previously, we have performed DFT calculations using cluster models of the proposed active surface center of the M1 phase to study the hydrogen abstraction steps from propane to p-allyl intermediate on the various metal sites [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…[25] We discussed in some detail the M2 catalyst at Irsee IV, where we used the ReaxFF reactive force field to resolve the partial occupations in the Rietveld crystal strucures to form a 2×3×4 supercell that resolved the structure into whole atoms. [26] We then built models of the stable surfaces and examined the activation of propene. We found that the surface V=O and Mo=O species could not activate propene, whereas most surface Te=O sites could.…”
Section: The Reaction Mechanism For Propane To Propene On the M1 Phasmentioning
confidence: 99%
“…Indeed we did this for the M2 phase using the ReaxFF reactive force field to find the optimum configuration, which required a 2×3×4 supercell. [26] A similar supercell for M1 would require 3840 atoms, far too large for QM. Thus previous computational studies have focused on developing algorithms to determine the exact locations of molybdenum and vanadium atoms rather than studying the reaction mechanism.…”
Section: The Mechanism For Activating the Propane Ch Bond In The M1 Pmentioning
confidence: 99%